ChemInform Abstract: Molecular Rare‐Earth‐Metal Hydrides in Non‐Cyclopentadienyl Environments. Issue 13 (March 2015) - Fegler, Waldemar; Venugopal, Ajay; Kramer, Mathias; Okuda, Jun
Abstract Review: [55 refs.